Effects of guided-reverse jigsaw instructional strategy on senior secondary school physics students’ achievement in Oyo State, Nigeria (2022)
The study determined the effects of guided-reverse instructional strategy on Physics Students ’ achievement in Senior Secondary Schools in Oyo State, Nigeria. Four hypotheses were tested at 0.05 level of significance. 73 students selected from two schools took part in the study. The instruments for data collection were twenty items Physics Achievement Test while Mean, standard deviation and t-test were used for the analysis of the data. A statistically significant deference exists in the mean academic achievement scores of students taught physics using guided-reverse jigsaw instructional strategy and those taught using conventional lecture method m favor of guided-reverse instructional strategy. Gender differences are of no statistically significant difference in the mean academic achievement scores for both experimental and control groups. The study recommends that physics teachers should adopt guided-reverse jigsaw instructional strategy.